Detección serológica de potato virus Y en chilto (Solanum betaceum) en Jujuy - Jaramillo, Margarita; Cabrera Mederos, Dariel; Ortiz, Claudio Manuel; Flores, Ceferino Rene; Trucco, Veronica Milagros; Nome Docampo, Claudia; Giolitti, Fabian (Asociación Argentina de Horticultura (ASAHo), 2025)
Poster